The influence of universities’ management on academic factors and students’ satisfaction: an empirical study through structural equation modelling - Jager, Johan W de (Prof. Ansie Lessing, 2019)
Institutions of higher education are facing intense competition as a result of globalisation. It has become increasingly important for institutions of higher education to realise the significant impact of rendering quality service and the impact it has on customer satisfaction. The aim of this study is to focus on the influence of Universities’ management practices on academic factors and the satisfaction levels of students. Three hundred and ninety one students from two South African universities were sampled at random to participate in the study. The study made use of exploratory factor analysis (EFA) followed by confirmatory factor analysis (CFA). Hypotheses testing, through the use of structural equation modelling (SEM) was finally implemented. The main results were as follows: Management-related factors have a strong impact on academic factors and academic factors have a strong impact on student satisfaction. Management as well as academic factors have a strong impact on student satisfaction. Consequently, special attention should be given by institutions’ management team in order to enhance the satisfaction level of students.